2003
DOI: 10.1021/bi0352825
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent, Irreversible Formation of Amyloid Fibrils by a Soluble Human Ataxin-3 Carrying a Moderately Expanded Polyglutamine Stretch (Q36)

Abstract: The protein ataxin-3 is responsible for Machado-Joseph disease/spinocerebellar ataxia type 3, a neurodegenerative disorder caused by the presence of an expanded polyglutamine tract. A previous investigation [Bevivino, A. E., and Loll, P. J. (2001) Proc. Natl. Acad. Sci. U.S.A. 98, 11955-11960] showed that a nonexpanded ataxin-3 (Q27) was fully soluble, whereas an expanded form (Q78) gave rise to amyloid fibrils. Here, we report investigations on three forms of ataxin-3 (i.e., human nonexpanded (Q26), moderatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
23
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 25 publications
6
23
1
Order By: Relevance
“…1. In accordance with previous studies (22,25,35,36), we observed preferential binding of the polyglutamine-specific antibody 1C2 for the longer variant, which lies at the cusp of toxicity in Machado-Joseph disease, although nonpathological proteins could also be recognized (Fig. 1C).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…1. In accordance with previous studies (22,25,35,36), we observed preferential binding of the polyglutamine-specific antibody 1C2 for the longer variant, which lies at the cusp of toxicity in Machado-Joseph disease, although nonpathological proteins could also be recognized (Fig. 1C).…”
Section: Resultssupporting
confidence: 92%
“…In light of this, and given that ataxin-3 fibrillization does not necessarily proceed via a partially unfolded state, it is possible that the solubility of the protein may be a key element involved in the process. This is also consistent with difficulties experienced by ourselves and others in producing satisfactory quantities of expanded ataxin-3 variants in soluble form (19,25) and also the well documented insolubility of polyglutamine peptides alone and their rapid propensity to form fibrils even at nonpathological lengths (20,23).…”
Section: Kinetic Analysis Of Acid-induced Denaturation Of Ataxin-3-supporting
confidence: 89%
See 3 more Smart Citations